2008
DOI: 10.1104/pp.108.116962
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Mature Etiolated Cucumber Hypocotyl Cell Wall Susceptibility to Expansin by Pretreatment with Fungal Pectinases and EGTA in Vitro

Abstract: Mature plant cell walls lose their ability to expand and become unresponsive to expansin. This phenomenon is believed to be due to cross-linking of hemicellulose, pectin, or phenolic groups in the wall. By screening various hydrolytic enzymes, we found that pretreatment of nongrowing, heat-inactivated, basal cucumber (Cucumis sativus) hypocotyls with pectin lyase (Pel1) from Aspergillus japonicus could restore reconstituted exogenous expansin-induced extension in mature cell walls in vitro. Recombinant pectate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 78 publications
3
39
0
Order By: Relevance
“…The basis for growth gradients in shoots has been examined by other approaches. Cell wall creep assays showed that the apical, rapidly growing regions of cucumber (Cucumis sativus) hypocotyls and coleoptiles are more responsive than nonelongating regions to the wall-loosening action of exogenous expansins (McQueen-Mason et al, 1992;Cosgrove and Li, 1993), potentially as a result of changes associated with pectin esterification (Zhao et al, 2008). This ties in with other studies implicating pectin deesterification in the decline of growth potential in basal regions of mung bean (Vigna radiata) hypocotyl (Goldberg and Prat, 1982).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The basis for growth gradients in shoots has been examined by other approaches. Cell wall creep assays showed that the apical, rapidly growing regions of cucumber (Cucumis sativus) hypocotyls and coleoptiles are more responsive than nonelongating regions to the wall-loosening action of exogenous expansins (McQueen-Mason et al, 1992;Cosgrove and Li, 1993), potentially as a result of changes associated with pectin esterification (Zhao et al, 2008). This ties in with other studies implicating pectin deesterification in the decline of growth potential in basal regions of mung bean (Vigna radiata) hypocotyl (Goldberg and Prat, 1982).…”
supporting
confidence: 67%
“…In contrast, pectic polysaccharide structure and dynamics showed pronounced changes along the elongation zone, with lower arabinan and galactan content, decreased esterification, reduced pectin mobility, and weaker water-pectin interactions in the apical-to-basal direction. In previous work, decreases in pectin esterification and increases in calcium crosslinking were associated with growth cessation in mung bean hypocotyls (Goldberg, 1984;Goldberg et al, 1986) and with loss of cell wall creep induced by expansins in cucumber hypocotyls (Zhao et al, 2008). Likewise, pectin mobility, as measured by SSNMR spin relaxation, was reduced in pectin-rich collenchyma from nongrowing (tall) stalks of celery (Apium graveolens) compared with shorter (still growing) stalks (Fenwick et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Because the basal sections of stipes lost their elongation capacity, but still displayed a weaker acid-induced short-term wall extension activity, we conclude that the weaker, non-protein-mediated, acid-induced short-term extension in stipe walls is not involved in stipe wall elongation growth. Thus far, non-protein-mediated short-term extension has not been reported in plant cell walls, and heated or denatured plant walls did not display any remaining short-term wall extension (Cosgrove, 1998;McQueen-Mason et al, 1992;Zhao et al, 2008). The nonprotein-mediated, heat-insensitive wall extension of stipes may be related to their specific chitin component in the stipe wall structure, which is lacking in plant cell walls (Bowman & Free, 2006;Ruiz-Herrera & Ortiz-Castellanos, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this can explain why acid induction is required for expansin-like protein-reconstituted wall extension in plants (Cosgrove 2000(Cosgrove , 2005 or in basidiomycetes (Fang et al, 2014). Regarding the fact that this heat-insensitive short-term wall extension shows a gradient that is high in the apical and low in the basal region, this gradient may indicate that some other cross-links, in addition to hydrogen bonds, may occur between polysaccharides in stipe walls along with cell wall maturation during the development of fruit bodies (Cabib & Arroyo, 2013;Zhao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation